Association between fatigue and cytokine profiles in patients with ischemic stroke - Kirchberger, Inge; Meisinger, Christa; Freuer, Dennis; Leone, Vincenza; Ertl, Michael; Zickler, Philipp; Naumann, Markus; Linseisen, Jakob (Frontiers in Neurology, 2023)
Background Chronic fatigue is a common symptom after a stroke. Studies suggested that chronic fatigue is caused by inflammatory or immunological processes but data are limited and contradictory. Thus, the present study aimed to identify specific biomarkers associated with fatigue in post-stroke patients and replicated the findings in a population-based study. Methods We investigated associations between 39 circulating biomarkers of inflammation and fatigue in 327 patients after an ischemic stroke included in the Stroke Cohort Augsburg (SCHANA) study and the “Metabolism, Nutrition and Immune System in Augsburg” (MEIA) study (n = 140). The Fatigue Assessment Scale (FAS) was used to assess the severity of fatigue. The serum concentrations of the biomarkers were measured using the Bio-Plex Pro™ Human Cytokine Screening Panel (Bio-Rad, USA). Multiple linear regression models adjusted for possible confounders were used to examine associations. Results In patients with stroke, SCGFb was inversely associated [−1.67, 95% confidence interval (CI) (−3.05; −0.29) p = 0.018], and in healthy subjects, G-CSF was positively associated [1.56, 95% CI (0.26; 2.87), p = 0.020] with an increasing FAS-score, while SCF was positively related in both samples [1.84, 95% CI (0.27; 3.42), p = 0.022 and 1.40, 95% CI (0.29; 2.52), p = 0.015]. However, after correction for multiple testing, all of these associations lost statistical significance. Conclusion The present findings suggested an association between the growth factor SCF and fatigue. Future research on cytokines as possible markers of fatigue should focus on a longitudinal design including a sufficiently large number of study participants to enable testing associations between certain cytokines and sub-groups of chronic fatigue.